A comparative clinical study on the efficacy of Vamana Karma (therapeutic emesis) and Virechana Karma (therapeutic purgation) procedures along with Shamana (palliative) therapy for the management of hypothyroidism - Ranajan, Mridul; Abhinav, Abhinav; Meena, Dinesh; Shalini, Shalini; Jaiswal, Awantika; Thakar, Anup B (International journal of health sciences, 2021)
Introduction: Hypothyroidism is a common endocrine disorder characterized by an underactive thyroid gland, leading to decreased production of thyroid hormones. In Ayurveda, hypothyroidism is often compared to the condition of decreased metabolic activity (~Dhatwagni-mandya) at the tissue level. A holistic Ayurvedic approach that includes Panchkarma (Bio purification and detoxification procedures) can be highly beneficial in the treatment of hypothyroidism. Aim: To evaluate the efficacy of Shodhana (Bio-purification) along with Shamana (Palliative) interventions in the management of hypothyroidism. Materials and Methods: Total 101 patients of hypothyroidism were randomly grouped into three. Patients registered in Group A (n=33) were treated with Vamana Karma along with Shaman Chikitsa, Group B treated with Virechana Karma along with Shaman Chikitsa and in group C treated with Shamana Chikitsa for 45 days. Results: Significant improvement found in thyroid profile with treatment in group A and BMI was significantly decreased in all three groups. Conclusion: Vamana followed by Shamana therapy was found more effective than other groups in thyroid function tests.